Embedded Software and Systems Second International Conference, ICESS 2005, Xi$1 (Ban, China, December 16-18, 2005. Proceedings /s - Yang, Laurence T.; Zhou, Xingshe; Zhao, Wei.; Wu, Zhaohui; Zhu, Yian.; Lin, Man.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
Welcome to the proceedings of the 2005 International Conference on Emb- ded Software and Systems (ICESS 2005) held in Xian, China, December 16-18, 2005. With the advent of VLSI system level integration and system-on-chip, the center of gravity of the computer industry is now moving from personal c- puting into embedded computing. Embedded software and systems are incre- ingly becoming a key technological component of all kinds of complex technical systems, ranging from vehicles, telephones, aircraft, toys, security systems, to medical diagnostics, weapons, pacemakers, climate control systems, etc. The ICESS 2005 conference provided a premier international forum for - searchers, developers and providers from academia and industry to address all resulting profound challenges; to present and discuss their new ideas, - search results, applications and experience; to improve international com- nication and cooperation; and to promote embedded software and system - dustrialization and wide applications on all aspects of embedded software and systems.
Keynote Speech -- Track 1: Embedded Hardware -- Track 2: Embedded Software -- Track 3: Real-Time Systems -- Track 4: Power-Aware Computing -- Track 5: Hardware/Software Co-design and System-On-Chip -- Track 6: Testing and Verification -- Track 7: Reconfigurable Computing -- Track 8: Agent and Distributed Computing -- Track 9: Wireless Communications -- Track 10: Mobile Computing -- Track 11: Pervasive/Ubiquitous Computing and Intelligence -- Track 12: Multimedia and Human-Computer Interaction -- Track 13: Network Protocol, Security and Fault-Tolerance -- Track 14: Workshop Selected Papers -- Keynote Speech.
Keywords: Computer science; Microprocessors; Computer communication systems; Special purpose computers; Software engineering; Operating systems (Computers).; Computer Science; Software Engineering/Programming and Operating Systems; Computer Communication Networks; Software Engineering; Operating Systems; Special Purpose and Application-Based Systems; Processor Architectures; Electronic books